Health Education Intervention Using Peer Group Approach for Adolescents in Addressing Delinquent Behavior - Ro'isah; Laili, Nurul (Al-Hijrah Indonesia, 2024)
Background: Adolescence is a transition period experienced by teenagers, and this period is prone to the emergence of delinquency problems. At this time, teenagers begin to determine and get to know their peers in daily interactions. Peers are an environmental factor in developing oneself optimally. Purpose: To determine the effect of health education interventions using a peer group approach on juvenile delinquency prevention behavior in Probolinggo. Methods: This research includes pre-experimental research with a one-group pre-post-test design. The sample population is all teenagers in Kali Buntu Village, Probolinggo Regency, with 60 teenagers. The sample is some teenagers who meet the research criteria using a simple random sampling technique, a total of 60 teenagers. This research is about juvenile delinquency prevention behavior, and the independent variable is health education intervention. The intervention was conducted by providing education using a peer group approach according to the SOP for 60 minutes. Data were collected using a questionnaire sheet and analyzed statistically using SPSS with the Marginal Homogeneity Test. Result: The research findings revealed that the preventive behavior before the intervention was essentially the same, and after the intervention, there was a significant change, indicating the influence of health education with a peer group approach on preventing adolescent delinquency (P=0.000 < α= 0.05). Conclusion: There is expected to be an improvement in knowledge, attitudes, and skills for preventing adolescent delinquency.